Radiographic response to neoadjuvant therapy in pleural mesothelioma should serve as a guide for patient selection for cytoreductive operations - Deboever, Nathaniel; Zhou, Nicolas; McGrail, Daniel J.; Tomczak, Katarzyna; Oliva, Jacqueline L.; Feldman, Hope A.; Parra, Edwin; Zhang, Jianjun; Lee, Percy P.; Antonoff, Mara B.; Hofstetter, Wayne L.; Mehran, Reza J.; et al. (Frontiers in Oncology, 2023)
Background: Malignant pleural mesothelioma (MPM) is associated with poor prognosis despite advances in multimodal therapeutic strategies. While patients with resectable disease may benefit from added survival with oncologic resection, patient selection for mesothelioma operations often relies on both objective and subjective evaluation metrics. We sought to evaluate factors associated with improved overall survival (OS) in patients with mesothelioma who underwent macroscopic complete resection (MCR).Methods: Patients with MPM who received neoadjuvant therapy and underwent MCR were identified in a prospectively maintained departmental database. Clinicopathologic, blood-based, and radiographic variables were collected and included in a cox regression analysis (CRA). Response to neoadjuvant therapy was characterized by change in tumor thickness from pre-therapy to pre-operative scans using the modified RECIST criteria.Results: 103 99 patients met the inclusion criteria. The median age of included patients was 64.78 years, who were predominantly male, had smoking and asbestos exposure, and who received neoadjuvant therapy. The median change in tumor thickness following neoadjuvant therapy was -16.5% (interquartile range of -49.7% to +14.2%). CRA demonstrated reduced OS associated with nonepithelioid histology (hazard ratio [HR]: 3.06, 95% confidence interval [CI]: 1.62-5.78, p<0.001), and a response to neoadjuvant therapy inferior to the median (HR: 2.70, CI: 1.55-4.72, p<0.001). Patients who responded poorly (below median) to neoadjuvant therapy had lower median survival (15.8 months compared to 38.2 months, p<0.001).Poor response to neoadjuvant therapy in patients with MPM is associated with poor outcomes even following maximum surgical cytoreduction and should warrant a patient-centered discussion regarding goals of care and may therefore help guide further therapeutic decisions.